2019
DOI: 10.1097/cin.0000000000000512
|View full text |Cite
|
Sign up to set email alerts
|

Nursing Students’ Technological Equipment Usage and Individual Innovation Levels

Abstract: Technological equipment is an indispensable part of many people's lives. In parallel with this development, the role of innovation is critical to nurses' ability to provide patient care. Today, nursing students have grown up with technology. Therefore, the field is expected to be more open to innovation in nursing care. It is thought that the use of technological equipment influences the level of innovation. The purpose of this study was to determine nursing students' technological equipment usage, individual … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
8
0
4

Year Published

2019
2019
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(12 citation statements)
references
References 7 publications
0
8
0
4
Order By: Relevance
“…22 However, in that study it was also found that the abilities of the students to innovatively define the existing problems of healthy individuals and/or those with medical conditions and to develop individually tailored solutions improved with the introduction of the course entitled "Care Technologies." [23][24][25] The mean personal life situation subscale score of working students was significantly higher compared with that of the unemployed students. "Personal life situation" relates to the personal aspects of the life of a healthy individual or someone with a medical condition, such as his or her beliefs and values, habits, activities, and preferences.…”
Section: Discussionmentioning
confidence: 99%
“…22 However, in that study it was also found that the abilities of the students to innovatively define the existing problems of healthy individuals and/or those with medical conditions and to develop individually tailored solutions improved with the introduction of the course entitled "Care Technologies." [23][24][25] The mean personal life situation subscale score of working students was significantly higher compared with that of the unemployed students. "Personal life situation" relates to the personal aspects of the life of a healthy individual or someone with a medical condition, such as his or her beliefs and values, habits, activities, and preferences.…”
Section: Discussionmentioning
confidence: 99%
“…BYÖ toplam puan ortalaması 70,67±5,86 (54-86) olup "Fikir Önderliği", "Değişime Direnç" ve "Risk Alma" alt boyutları puan ortalamaları ise sırasıyla 25,36±3,66 (15-35), 29,37±3,20 (18-38) ve 15,93±2,03 (8)(9)(10)(11)(12)(13)(14)(15)(16)(17)(18)(19)(20) idi.…”
Section: Bulgularunclassified
“…19 Turan ve ark.nın araştırmasında, hemşirelik öğrencilerinin BYÖ puan ortalaması 61,02±8,89'dur ve öğrenciler "sorgulayıcı" özelliklere sahiptir. 20 Bodur'un araştırmasında, hemşirelik öğrencilerinin BYÖ'den aldıkları puan ortalaması 63,12±7,70 olup öğrencilerin "sorgulayıcı" ve "öncü" özelliklere sahip oldukları belirlenmiştir. 11 Başoğlu ve Durmaz Edeer'in araştırmasında, hemşirelik öğrencilerinin %44,1'i öncü ve %42,4'ü sorgulayıcı olarak saptanmıştır.…”
Section: Bulgularunclassified
“…One of the necessities of today’s changing world is innovation [ 1 ]. Individual innovation refers to the ability to take risks in the face of newness, adapt and adopt, apply and tolerate, and experience new things [ 2 ]. Individual innovation means the desire to search and find new approaches to solve a problem using new and already existing resources [ 3 ].…”
Section: Introductionmentioning
confidence: 99%
“…They are also expected to have an innovative way of thinking so that they can play their innovative role effectively [ 17 ]. Therefore, individual innovation seems an essential attribute for nursing students [ 2 ]. In Taiwan, creativity and innovation are considered as one of the main competencies of nursing students [ 18 ].…”
Section: Introductionmentioning
confidence: 99%